Pemikiran G. H. A. Juynboll tentang Hadis - Mahmudah, Nur (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2013)
The outsaider studies that represented by the tradition of orientalism or islamism which continues until now are shows the dynamics of the hadith study from time to time. And one of the sect of hadith study that developed in the western wes skeptical sect. To analyze the thought of skeptical sect in the hadith study at western, this paper will discuss the Juynboll thought in hadith and the things that tangent to it which is including explored an attempt the use of the methodology or theory in the Western studies whitin certain limits for the assessment of hadith. A part from the implications and motives that sometimes becomes the background for hadith assessment as seen in the long history of islamic studies (including the hadith in it), a serious challenge from Western scholars to prove the historicity of the hadith is part of the Muslim scholary duty to provide academic and scintific answers, not just a description of the normative-apologist.